Regional newspaper coverage of shale gas development across Ohio, New York, and Pennsylvania: Similarities, differences, and lessons. (January 2016) - Ashmoore, Olivia; Evensen, Darrick; Clarke, Chris; Krakower, Jennifer; Simon, Jeremy
Abstract: In communities experiencing shale gas development, the local media are an important information source on potential impacts of development; their coverage generates and spreads social representations of this issue. We examine representations of natural gas development through a content analysis of six regional newspapers in the northern United States ( n  = 1, 958 articles) – two each in Ohio, New York, and Pennsylvania. Previous research showed similarities between the New York and Pennsylvania newspapers; differences emerged in nearby Ohio's coverage. In Ohio, similar percentages of articles mentioned economic impacts as in Pennsylvania and New York, but significantly fewer articles mentioned environmental or social impacts. Furthermore, valence of economic and social impacts was notably more positive in Ohio. This analysis highlights nuances inherent in regional discourse about shale gas development. In turn, these differences have implications for: (1) how politicians, journalists, activists, and researchers can better communicate about shale gas development, (2) policy/regulation of development, and (3) future research on social representations of emergent forms of energy extraction. We suggest the need, in social science research on energy development, to examine societal-level (not merely individual) influences on perceptions and to account for nuances inherent in regional variation – infrequently manifest in national sample studies.